Substantial protection against MPTP-associated Parkinson's neurotoxicity in vitro and in vivo by anti-cancer agent SU4312 via activation of MEF2D and inhibition of MAO-B. (November 2017) - Guo, Baojian; Hu, Shengquan; Zheng, Chengyou; Wang, Hongyu; Luo, Fangcheng; Li, Haitao; Cui, Wei; Yang, Xifei; Cui, Guozhen; Mak, Shinghung; Choi, Tony Chung-Lit; Ma, Edmond Dik-Lung; et al.
Abstract: We have previously demonstrated the unexpected neuroprotection of the anti-cancer agent SU4312 in cellular models associated with Parkinson's disease (PD). However, the precise mechanisms underlying its neuroprotection are still unknown, and the effects of SU4312 on rodent models of PD have not been characterized. In the current study, we found that the protection of SU4312 against 1-methyl-4-phenylpyridinium ion (MPP + )-induced neurotoxicity in PC12 cells was achieved through the activation of transcription factor myocyte enhancer factor 2D (MEF2D), as evidenced by the fact that SU4312 stimulated myocyte enhancer factor 2 (MEF2) transcriptional activity and prevented the inhibition of MEF2D protein expression caused by MPP +, and that short hairpin RNA (ShRNA)-mediated knockdown of MEF2D significantly abolished the neuroprotection of SU4312. Additionally, Western blotting analysis revealed that SU4312 potentiated pro-survival PI3-K/Akt pathway to down-regulate MEF2D inhibitor glycogen synthase kinase-3beta (GSK3β). Furthermore, using the in vivo PD model of C57BL/6 mice insulted with 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP), we found that intragastrical administration of SU4312 (0.2 and 1 mg/kg) greatly ameliorated Parkinsonian motor defects, and restored protein levels of MEF2D, phosphorylated-Ser473-Akt and phosphorylated-Ser9-GSK3β. Meanwhile, SU4312 effectively reversed the decrease in protein expression of tyrosine hydroxylase in substantia nigra pars compacta dopaminergic neurons, inhibited oxidative stress, maintained mitochondrial biogenesis and partially prevented the depletion of dopamine and its metabolites. Very encouragingly, SU4312 was able to selectively inhibit monoamine oxidase-B (MAO-B) activity both in vitro and in vivo, with an IC50 value of 0.2 μM. These findings suggest that SU4312 provides therapeutic benefits in cellular and animal models of PD, possibly through multiple mechanisms including enhancement of MEF2D through the activation of PI3-K/Akt pathway, maintenance of mitochondrial biogenesis and inhibition of MAO-B activity. SU4312 thus may be an effective drug candidate for the prevention or even modification of the pathological processes of PD. Graphical abstract: Highlights: SU4312 inhibits mitochondria-dependent apoptotic pathway caused in MPP + -treated PC12 cells. SU4312 ameliorates Parkinsonian motor defects in MPTP-treated mice. SU4312 stimulates MEF2 transcriptional activity under both basal and pathological conditions. SU4312 enhances MEF2 activity through the activation of PI3-K/Akt/GSK3β. SU4312 inhibits MAO-B activity in vitro and in vivo.